An evaluation of lignocellulosic solutions from OPEFB pulping process as demulsifiers for crude oil emulsion demulsification. (18th July 2019) - Busu, Tengku Nur Zulaikha Tengku Malim; Saman, Norasikin; Mohtar, Safia Syazana; Md Noor, Ahmad Mujahid; Hassan, Onn; Ali, Noorhalieza; Mat, Hanapi
Abstract: Lignocellulosic solutions from oil palm empty fruit bunch (OPEFB) organosolv pulping process are used as demulsifiers for demulsification of crude oil emulsion using a model of water-in-oil emulsion of crude oil and brine solution. The results indicate that the demulsification performance was favored when only lignin compound was contained in the demulsifier. The phase separation capacity and rate were strongly affected by brine pH values, temperatures and demulsifier dosages. Complete phase separation capacity was achieved at the optimum conditions. The separated oil and water are qualified for refining process and water treatment, respectively, making it promising as a demulsifier.